Improved inhibitors of trypanothione reductase by combination of motifs: synthesis, inhibitory potency, binding mode, and antiprotozoal activities - Eberlein, Christian; Lauber, Birgit Sophia; Fankhauser, Daniel; Kaiser, Marcel; Brun, Reto; Krauth-Siegel, Renate; Diederich, François (ChemMedChem, 2011)
Trypanothione reductase (TR) is an essential enzyme in the trypanothione-based redox metabolism of trypanosomatid parasites. This system is absent in humans and, therefore, offers a promising target for the development of selective new drugs against African sleeping sickness and Chagas' disease. Over the past two decades, a variety of nonpeptidic small-molecule ligands of the parasitic enzyme were discovered. A current goal is to decipher the binding mode of these known inhibitors in order to optimize their structures. We analyzed the binding mode of recently reported 1-(1-(benzo[b]thiophen-2-yl)cyclohexyl)piperidine (BTCP) analogues using computer modeling methods. This led us to conclude that the analogues occupy a different region of the active site than the diaryl sulfide-based class of inhibitors. A combination of the two motifs significantly increased affinity for the enzyme compared to the respective parent compounds. The newly synthesized conjugates exhibit Kic values for TR as low as 0.51±0.1 μM and high selectivity for the parasitic enzyme over the related human glutathione reductase (hGR), as was predicted by our molecular modeling studies. In vitro studies showed IC50 values in the low micromolar to submicromolar range against Trypanosoma brucei rhodesiense, often in combination with low cytotoxicity against mammalian cells. Interestingly, even stronger activities were found against Plasmodium falciparum.
First published: 16 December 2010
Gesehen am 04.04.2022